Perilaku hand hygiene tenaga kesehatan di RSUP Sanglah tahun 2018 - Made Dwi Andhika Yogiswara; Ni Luh Putu Ariastuti; Putu Aryani (Intisari Sains Medis, 2019)
Background: Low hand hygiene behavior is a very detrimental and a cause of health care associated infection and is a problem faced by patients and the medical profession at this time. The purpose of this study was to find out the distribution of hand hygiene behavior among healthcare professionals in Sanglah General Hospital Denpasar.Method: This study was conducted using a descriptive method with a cross-sectional study design carried out in the polyclinic and inpatients ward at Sanglah General Hospital in September to November 2018.Results: From the 96 study samples, 82.3% had good compliance with hand hygiene standards and 68.7% had a positive perception of hand hygiene. Women are more obedient than men towards the implementation of hand hygiene and doctors is the lowest profession to have a level of adherence to hand hygiene.Conclusion: Perception and compliance with hand hygiene in medical personnel at Sanglah General Hospital Denpasar has been very good, but it still needs to be improved so that all medical personnel perform hand hygiene procedures as a routine practice for the sake of infection prevention and control.